Mini implant overdenture with magnetic retention in the prosthetic case - Yunita Feby Ramadhany; Irfan Dammar (Makassar Dental Journal, 2020)
Background: The resorption of the mandibular alveolar bone is a common problem in the edentulous jaw, causing the alveolar ridge to become flat. This can lead to poor complete denture function and an unbalanced occlusion. Therefore, treatment is needed to obtain adequate retention and stability in edentulous mandible. Today, mini implant overdenture using magnetic retention is often used as a treatment for edentulous mandible. Objective: To review the literature on mini implant overden-ture using magnetic retention in prosthodontic cases. Discussion: Implant overdenture is a complete or partial denture covering the implant used as a support. Stability and retention of dentures in the long term can be achieved by using a small diameter implant called mini dental implant that is mounted directly on the alveolar ridge using magnets. Conclusion: Mini implant overdenture can be used in cases of edentulous mandible to obtain good retention and stability.